Rice and irrigation in West Africa: achieving food security with agricultural water management strategies - Katic, Pamela G.; Namara, Regassa E.; Hope, Lesley; Owusu, E.; Fujii, H. (Elsevier, 2013)
West Africa's rice imports currently satisfy 70% of the soaring local demand, worsening the food vulnerability of an increasingly urbanized population. Despite considerable rice-growing potential, lack of water control systems, access to improved seeds, agrochemicals and appropriate mechanization have resulted in modest production growth rates, unable to alter the region's dependency on imported rice. Governments aim to boost production with import duties and input subsidies. However, questions remain as to whether these policies enable the rice sector to respond to changing consumers preferences for high grade rice and to contribute to national economic growth. We present the results from a Policy Analysis Matrix (PAM) on rice production in Ghana, Burkina Faso and Niger and under three water management systems: irrigation (public scheme), supplemented rain-fed (rainfall aided by autonomously-sourced water supplies) and purely rain-fed. Our results show that policy interventions in these West African countries (i.e., input subsidies and import taxes) did not significantly enhance the profitability of rice production to farmers due to the effect of market failures (limited capital access and non-competitive market for rice) and the low quality of local milled rice. The PAM results point strongly to the importance of improving rice quality and yields through more efficient water management and post-harvest handling/processing and targeted breeding to match consumers' preferences.